Robert James Forbes (1900–1973) – chemicus-archeoloog, techniekhistoricus, wetenschapshistoricus - Homburg, Ernst (Studium, 2013)
Robert James Forbes (1900–1973) – chemicus-archeoloog, techniekhistoricus, wetenschapshistoricus